Interdisciplinary Approach to Identifying the Educational Contribution of Tourism to Local Education Development: A Systematic Literature Review - Yohanis Tarukallo (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the educational contributions of tourism to the development of local education in rural areas of Indonesia through an interdisciplinary approach. The research employs a Systematic Literature Review (SLR) method based on the PRISMA protocol, using data sources from the Scopus database covering the period 2020–2025. Out of a total of 688 identified documents, 20 scholarly articles meeting the inclusion criteria were thematically analyzed. The findings indicate that tourism functions as a social learning system integrating cultural, environmental, social, and economic dimensions. Three primary models were identified: the culture- and local identity–based model, the environment- and sustainability–based model, and the creative economy– and community empowerment–based model. Furthermore, the study reveals research gaps in the form of limited quantitative empirical evidence, methodological constraints, and insufficient integration between educational and tourism policies. This research proposes a conceptual framework, the Tourism–Education Synergy Framework, which conceptualizes tourism as a learning ecosystem operating through knowledge transfer, social capacity building, and value transformation. In conclusion, tourism holds significant potential to enhance the educational capacity of rural communities and to foster sustainable development grounded in local learning.